Media law after Leveson: a view from the coalface - Phillips, G (2013)
In this policy brief, the Guardian’s Director of Editorial Legal Services Gillian Phillips presents her perspective on the post-Leveson media law landscape, arguing that journalists are being submerged in a complex network of more and more law and regulation, which threatens not only to restrict but to criminalize journalists’ conduct.